Simulating fault instability induced by fluid injection in in-situ experiments - Lee, Audrey Hui Xing (Nanyang Technological University, 2025)
The project investigates how fluid injection can affect fault stability and quantifies the impacts using a numerical fault model that integrates fault dynamics with fluid flow. To simulate fluid flow, Finite Difference Method and Finite Element Method were benchmarked for model accuracy. While both methods produced comparably accurate results, the model leverages Finite Difference Method for its computational efficiency to model fluid flow in a fault. Across a wide range of permeability profiles, from simple to increasingly complex, the model produces a broad spectrum of seismic responses. The numerical results suggest that differences in permeability profiles across models notably influence spatial and temporal evolution of pore fluid pressure and have pronounced implications on induced seismicity. As a preliminary finding, permeability appears to strongly influence the timing (immediate or delayed), extent (full or partial), and characteristics (seismic or aseismic) of the fault’s response. Over time, even models with the same average permeability exhibit increasingly divergent seismic responses, highlighting the sensitivity of spatial variations in permeability on fault dynamics. Despite its simplified, 1D setup, the model is flexible and adaptable to various contexts, effectively capturing key fault-fluid coupling mechanisms while requiring significantly fewer computational resources than more complex and intricate models.